2020
DOI: 10.1161/circimaging.119.009675
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Risk Factors for Dilatation of the Proximal Aorta in a Large Cohort of Children With Bicuspid Aortic Valve

Abstract: Background: Patients with bicuspid aortic valve (BAV) have a higher risk of developing aortic valve dysfunction and progressive proximal aorta dilatation, which can lead to aortic dissection. To this day, identification of children at risk of developing severe aortic dilatation during their pediatric follow-up is still challenging because most studies were restricted to adult subjects. The overarching goal of this study was to identify risk factors of aortic dilatation in children with BAV. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 47 publications
2
20
0
1
Order By: Relevance
“…However, fetuses with aortic valve stenosis were excluded from our cohort as were fetuses with other lesions such as coarctation of the aorta with a known association with bicuspid aortic valve. However, in pediatric patients with BAV early signs of dilated ascending aorta in the absence of aortic stenosis or regurgitation and irrespective of the pattern of aortic cusp fusion has been reported 1–3 . Abnormal flow dynamics in the ascending aorta have been implicated in dilation of the ascending aorta in the presence of a bicuspid aortic valve, even in the absence of aortic valve stenosis 3,13 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, fetuses with aortic valve stenosis were excluded from our cohort as were fetuses with other lesions such as coarctation of the aorta with a known association with bicuspid aortic valve. However, in pediatric patients with BAV early signs of dilated ascending aorta in the absence of aortic stenosis or regurgitation and irrespective of the pattern of aortic cusp fusion has been reported 1–3 . Abnormal flow dynamics in the ascending aorta have been implicated in dilation of the ascending aorta in the presence of a bicuspid aortic valve, even in the absence of aortic valve stenosis 3,13 .…”
Section: Resultsmentioning
confidence: 99%
“…Dilatation of the ascending aorta is well described in children and adults most commonly in association with a bicuspid aortic valve (BAV) or connective tissue disorders such as Marfan syndrome and Loeys‐Dietz syndrome. With respect to BAV, which is present in 1%–2% of the population, recent data has confirmed that dilation of the ascending aorta may be present in infancy 1–3 . This is clinically important because severe dilatation of the ascending aorta is associated with an increased risk of aortic dissection 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AS is a very common valve disease, affecting between 2% and 4% of adults over the age of 65, and is associated with high mortality once it becomes symptomatic [ 1 ]. While tricuspid aortic valve degeneration is the most prevalent cause of AS in older individuals, bicuspid aortic valve degeneration is the most common cause of AS in younger people, with AS being one of the key determinants of ascending aortic dilatation in those patients [ 6 , 7 ]. HT has a high prevalence among patients with AS, leading to worse LV remodeling and faster degeneration and calcification of the valve [ 3 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Bicuspid aortic valve (BAV) is associated with aortic root dilation and dissection in adults, but the age and conditions when dilation begins are unknown Patients with bicuspid aortic valve (BAV) have a higher risk of developing aortic valve dys-function and progressive proximal aorta dilatation, which can lead to aortic dissection. To this day, the identification of children at risk of developing severe aortic dilatation during their pediatric follow-up is still challenging because most studies were restricted to adult subjects (Blais et al, 2020).…”
Section: Introductionmentioning
confidence: 99%